2021
DOI: 10.3389/fmed.2021.762930
|View full text |Cite
|
Sign up to set email alerts
|

Lactitol Supplementation Modulates Intestinal Microbiome in Liver Cirrhotic Patients

Abstract: Background: Cirrhosis is a common chronic liver disease characterized by irreversible diffuse liver damage. Intestinal microbiome dysbiosis and metabolite dysfunction contribute to the development of cirrhosis. Lactitol (4-β-D-galactopyranosyl-D-glucitol) was previously reported to promote the growth of intestinal Bifidobacteria. However, the effect of lactitol on the intestinal microbiome and fecal short-chain fatty acids (SCFAs) and bile acids (BAs) and the interactions among these factors in cirrhotic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Research findings have shown that the human gut microbiota can produce a variety of metabolites including short chain fatty acids, such as acetic acid, propionic acid, and butyric acid, which are produced by the decomposition of undigested dietary components [12] . Moreover, vitamin B and K affect the metabolism of the human body, thereby playing significant roles in pathogenesis of obesity, metabolic syndrome, diabetes, NAFLD, allergic reaction, inflammatory bowel disease and tumorigenesis in case of intestinal microecological imbalance [13] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research findings have shown that the human gut microbiota can produce a variety of metabolites including short chain fatty acids, such as acetic acid, propionic acid, and butyric acid, which are produced by the decomposition of undigested dietary components [12] . Moreover, vitamin B and K affect the metabolism of the human body, thereby playing significant roles in pathogenesis of obesity, metabolic syndrome, diabetes, NAFLD, allergic reaction, inflammatory bowel disease and tumorigenesis in case of intestinal microecological imbalance [13] …”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Moreover, vitamin B and K affect the metabolism of the human body, thereby playing significant roles in pathogenesis of obesity, metabolic syndrome, diabetes, NAFLD, allergic reaction, inflammatory bowel disease and tumorigenesis in case of intestinal microecological imbalance. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary cereal and yogurt intakes have been shown to be associated with high gut microbiota diversity and low hospitalization rates in patients with cirrhosis, which is possibly due to increased metabolism of short-chain fatty acids and probiotics ( 64 ). The supplementation of lactitol has been shown to reduce the load of pathogenic genes ARGs and VFGs in the intestinal flora; reduce the abundance of pathogenic bacteria associated with liver cirrhosis, such as Klebsiella ; increase the abundance of beneficial bacteria, such as Bifidobacterium ; and improve the prognosis of liver cirrhosis ( 65 ). Intestinal microbiota dysregulation is improved after transection of the hepatic branch vagus nerve in mice, which may be related to the overgrowth of potentially pathogenic bacteria enhanced by the vagus during cirrhosis ( 66 ).…”
Section: Gut Microbiota and Hepatobiliary Principal Diseasesmentioning
confidence: 99%
“…fermentium and L . oris ) but decreased the abundance of Klebsiella pneumonia in patients with liver cirrhosis [ 119 ]. There showed an improved abundance of Bifidobacterium and the reductions of the B .…”
Section: Sugar Alcoholsmentioning
confidence: 99%